2018
DOI: 10.1128/aac.02004-17
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Gentamicin Exposure in Neonates and Infants Calls into Question Its Current Dosing Recommendations

Abstract: Optimal dosing of gentamicin in neonates is still a matter of debate despite its common use. We identified gentamicin dosing regimens from eight international guidelines and seven Swiss neonatal intensive care units. The dose per administration, the dosing interval, the total daily dose, and the demographic characteristics between guidelines were compared. There was considerable variability with respect to dose (4 to 6 mg/kg), dosing interval (24 h to 48 h), total daily dose (2.5 to 6 mg/kg/day), and patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Reduced target attainment of antibiotics is common in critically ill neonates and children. Other studies that used population, dose, dose interval, and pharmacodynamic targets relatively similar to those in our study found similar results for vancomycin [ 15 , 16 ] and gentamicin [ 17 ]. De Cock et al [ 15 ] showed an even lower target attainment of vancomycin in PICU patients of only 8% compared with our 33.9%.…”
Section: Discussionsupporting
confidence: 88%
“…Reduced target attainment of antibiotics is common in critically ill neonates and children. Other studies that used population, dose, dose interval, and pharmacodynamic targets relatively similar to those in our study found similar results for vancomycin [ 15 , 16 ] and gentamicin [ 17 ]. De Cock et al [ 15 ] showed an even lower target attainment of vancomycin in PICU patients of only 8% compared with our 33.9%.…”
Section: Discussionsupporting
confidence: 88%
“…They have a reduced number of nephrons at birth and are often exposed to nephrotoxic drugs (i.e., aminoglycosides), while nephrogenesis is still ongoing [136]. TDM is advised for treatment beyond three days [137]. Preterm infants are at higher risk of overdosing due to the immature renal function [90]: acute kidney injury is considered an independent predictor of mortality, especially when the birthweight is less than 1500 g, and different biomarkers and definitions have been identified for the early detection of renal damage in these neonates, however they need validation [138].…”
Section: Preterm Infantsmentioning
confidence: 99%
“…During this earliest stage mortality is directly related to the effects of the life-threatening infection and managing toxicity is less central. As the causative organism generally remains unknown, selection of the antibiotic regimen needs to take into account the overall epidemiology of sepsis in the age group of the patient ( 19 ).…”
Section: Optimization Of Antibiotic Therapy In Sepsis: Empirical Vs mentioning
confidence: 99%
“…Shifts in MIC can lead to a situation where dosing recommendations need to be revised to achieve optimal treatment. For gentamicin, for example, an increase in MIC from 0.5 to 1.0 mg/L means that, in order to achieve similar efficacy (similar ratio of Cmax/MIC ), the dose should be increased from 5 to 7.5 mg/kg in neonates ( 19 ).…”
Section: Understanding the Link Between Antibiotic Exposure And Micromentioning
confidence: 99%
See 1 more Smart Citation